THE USE OF INLAY PATTERN RESIN AS AN ABUTMENT CROWN TEMPLATE FOR REMOVABLE PARTIAL DENTURES: CLINICAL REPORT: PENGGUNAAN POLA RESIN INLAY SEBAGAI MODEL TIRUAN MAHKOTA GIGI PENYANGGA PADA PEMBUATAN GIGI TIRUAN SEBAGIAN LEPASAN: LAPORAN KASUS - Naliani, Silvia; Bonifacius, Setyawan; Martono, Hadisusanto Ali (TALENTA, 2017)
Patients with removable partial denture need abutment tooth as retainer for the clasp. In some cases, this tooth requires endodontic treatment or even jacket crown so it can be used as a clasp retainer. For patient with removable partial denture, post core and crown fabrication in abutment teeth require adjustments to the crown to fit with denture clasp. First case, a 23-year-old male patient with fractured lower second premolar tooth because of previous metal restoration failure and had been treated with root canal treatment. The tooth was used as an abutment for removable partial denture that was still in good condition. The tooth was later treated with cast post and core with PFM (Porcelain fused to metal) crown. Second case, a 60-year-old female patient came to the clinic with a complaint of fracture in upper first premolar. This tooth was also used as abutment for maxillary framework partial denture. A template made of pattern resin was made to reproduce the dentures for both cases. Acrylic resin has good accuracy and stability to reproduce parts of the denture. The advantage of this technique is that patients can use their denture during fabrication of the crown.